2020
DOI: 10.1186/s12986-020-00523-2
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor is closely related to glucose metabolism, insulin sensitivity and insulin secretion in the second trimester: a case–control study in Chinese

Abstract: Objective Inflammation-related factors have been shown to play a significant role throughout pregnancy. In this study, we aimed to explore the relationships between selected inflammatory cytokines and gestational diabetes (GDM) in Chinese pregnant women. Design and methods This was a 1:1 matched case–control study that included 200 pairs of subjects in the second trimester and 130 pairs of subjects in the third trimester. Serum levels of nerve growth factor (NGF), Interleukin-6 (IL-6), leptin, Interleukin-8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Notably, this increment in tear SP was significantly associated with the increase in CNFD, demonstrating that tear SP may serve as a surrogate biomarker for corneal nerve regeneration in concordance with previous studies illustrating a significant correlation between tear SP and CNFD ( 42 , 43 ). Tear NGF concentrations were also found to be significantly higher in the patients with diabetes than in control subjects, which could be due to 1 ) a consequence of neuroinflammation ( 44 ), 2 ) a compensatory reaction to decreased corneal nerves ( 44 ), 3 ) an impaired uptake and transportation system of NGF in patients with diabetes ( 45 , 46 ), or 4 ) a protective response to degenerative nerves ( 47 ).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, this increment in tear SP was significantly associated with the increase in CNFD, demonstrating that tear SP may serve as a surrogate biomarker for corneal nerve regeneration in concordance with previous studies illustrating a significant correlation between tear SP and CNFD ( 42 , 43 ). Tear NGF concentrations were also found to be significantly higher in the patients with diabetes than in control subjects, which could be due to 1 ) a consequence of neuroinflammation ( 44 ), 2 ) a compensatory reaction to decreased corneal nerves ( 44 ), 3 ) an impaired uptake and transportation system of NGF in patients with diabetes ( 45 , 46 ), or 4 ) a protective response to degenerative nerves ( 47 ).…”
Section: Discussionmentioning
confidence: 98%
“…This is supported by case-control studies reporting increased circulating IL-8 levels in GDM patients, compared to healthy pregnancies [ 115 , 176 , 179 , 180 ]. However, comparable concentrations of IL-8 in the plasma of GDM patients vs. healthy pregnant women are also reported [ 167 , 184 , 185 ], as well as a lower IL-8 level in early pregnancy [ 184 ]. These inter-study inconsistencies probably emerge from the differences in the applied protocols and assays.…”
Section: Il-6 and Il-8 In Selected Pregnancy Pathologiesmentioning
confidence: 99%
“…Intriguingly, NGF levels in rat uterus are reduced during middle and late pregnancy compared to controls, which does correlate with known myometrial nerve degeneration 45 . Similarly, NGF expression is elevated in diabetes mellitus and it was shown to be a protective factor in diabetic neuropathy and vasculopathy [50][51][52][53] , but was also elevated and implicated in insulin resistance in gestational diabetic Chinese women in the second trimester 54 . Lobos et al, also demonstrated that proNGF levels increase during gestation possibly due to impaired processing of the pro form to the mature form 44,45 .…”
mentioning
confidence: 99%